2013
DOI: 10.1111/sltb.12044
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hope and Optimism in Suicide Risk for American Indians/Alaska Natives

Abstract: There are some American Indian/Alaska Native communities that exhibit high rates of suicide. The interpersonal theory of suicide (Joiner, 2005) posits that lethal suicidal behavior is likely preceded by the simultaneous presence of thwarted belongingness, perceived burdensomeness, and acquired capability. Past research has shown that hope and optimism are negatively related to suicidal ideation, some of the constructs in the interpersonal theory of suicide, and suicide risk for the general population. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 41 publications
6
49
2
Order By: Relevance
“…Similar findings have demonstrated that a lack of positive future expectancies is a better predictor of later suicidal ideation than hopelessness (O’Connor et al, 2008). Hope and optimism have also been investigated as protective factors for suicide thoughts and behaviors (O’Keefe & Wingate, 2013). To better investigate these constructs, Osman and colleagues developed a Future Disposition Inventory (FDI), which assesses both positive and negative orientation to the future for the purposes of assessing suicide risk (Osman et al, 2010) and has been shown to be an effective measure of hopelessness and optimism related to suicidal ideation (Bryan et al, 2013).…”
Section: Future-oriented Cognitionsmentioning
confidence: 99%
“…Similar findings have demonstrated that a lack of positive future expectancies is a better predictor of later suicidal ideation than hopelessness (O’Connor et al, 2008). Hope and optimism have also been investigated as protective factors for suicide thoughts and behaviors (O’Keefe & Wingate, 2013). To better investigate these constructs, Osman and colleagues developed a Future Disposition Inventory (FDI), which assesses both positive and negative orientation to the future for the purposes of assessing suicide risk (Osman et al, 2010) and has been shown to be an effective measure of hopelessness and optimism related to suicidal ideation (Bryan et al, 2013).…”
Section: Future-oriented Cognitionsmentioning
confidence: 99%
“…Snyder (, p. 251) suggests that agency “takes on special significance when people encounter impediments” and may be particularly important for building resilience in a marginalized population, such as in gay men. Previous studies demonstrate associations between high levels of agency and lower levels of thwarted belongingness (Anestis et al., ; Davidson et al., ) and high levels of agency and lower levels of suicidal behavior (O'Keefe & Wingate, ; Wai et al., ).…”
mentioning
confidence: 96%
“…Hope is defined as a cognitive state involving two components, agency —the perceived ability to motivate oneself to achieve one's goals and pathways —the perceived ability to cognitively plan viable routes to goals (Snyder, ). Previous studies have demonstrated associations between high levels of hope and low levels of thwarted belongingness (Anestis, Moberg, & Arnau, ; Davidson, Wingate, Slish, & Rasmussen, ) and between high levels of hope and low levels of suicidal ideation (O'Keefe & Wingate, ; Tucker et al., ). Furthermore, Hollingsworth, Wingate, Tucker, O'Keefe, and Cole () found in African American adults that hope moderated the relationship between thwarted belongingness and suicidal ideation, while controlling for depressive symptoms.…”
mentioning
confidence: 96%
“…Recent investigations suggest that some factors such as social support (Hirsch and Barton, 2011), meaning in life (Kleiman and Beaver, 2013), and positive affect (Hirsch et al, 2009) are associated with fewer suicidal thoughts and behaviors. Preliminary research regarding optimism (defined as generalized expectations for a positive future) consistently indicates that it is also inversely related to suicidal thoughts and behaviors (Bryan et al, 2013, Chang et al, 2013, Hirsch et al, 2007, O’Keefe and Wingate, 2013). …”
mentioning
confidence: 99%